Dog bites and maxillofacial surgery: what can we do?. Issue 6 (July 2015) - Mannion, C.J.; Graham, A.; Shepherd, K.; Greenberg, D.
Abstract The number of injuries caused by dog bites is increasing in the United Kingdom. We review patients admitted with dog bites to a single maxillofacial department in a district general hospital over a 21-month period. Data include patients' characteristics, and the site and severity of injury. The relationship of the victim to the animal and its breed and classification were added where possible. In total, 65 patients, mean age 22 years (range 1–71, median 14) were included. There were 84 wounds, and their site and severity were recorded according to the Lackmann classification. Twelve different breeds of dog were responsible for the bites. An appreciable proportion of those injured were young children. Educational strategies should aim to reduce the incidence of all dog bites, particularly in young children, as their needs after initial treatment are complex. We propose specific strategies to reduce the number of these injuries.